Enhanced stability in CO2 of Ta doped BaCe0.9Y 0.1O3-δ electrolyte for intermediate temperature SOFCs - Radojković, A.; Žunić, M. [UNESP]; Savić, S. M.; Branković, G.; Branković, Z. (Elsevier, 2013)
The influence of Ta concentration on the stability of BaCe 0.9-xTaxY0.1O3-δ (where x=0.01, 0.03 and 0.05) powders and sintered samples in CO2, their microstructure and electrical properties were investigated. The ceramic powders were synthesized by the method of solid state reaction, uniaxially pressed and sintered at 1550 °C to form dense electrolyte pellets. A significant stability in CO2 indicated by the X-ray analysis performed was observed for the samples with x≥0.03. The electrical conductivities determined by impedance measurements in the temperature range of 550-750 °C and in various atmospheres (dry argon, wet argon and wet hydrogen) increased with temperature but decreased with Ta concentration. The highest conductivities were observed in the wet hydrogen atmosphere, followed by those in wet argon, while the lowest were obtained in the dry argon atmosphere for each dopant concentration. The composition with Ta content of 3 mol% showed satisfactory characteristics: good resistance to CO2 in extreme testing conditions, while a somewhat reduced electrical conductivity is still comparable with that of BaCe0.9Y0.1O3-δ. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: A. Powders: solid state reaction; C. Electrical properties; D. Perovskites; Argon atmospheres; Ceramic powder; Dopant concentrations; Electrical conductivity; Enhanced stability; Hydrogen atmosphere; Impedance measurement; Intermediate temperatures; Powders: solid state reactions; Sintered samples; Ta content; Temperature range; Testing conditions; Various atmosphere; Electric conductivity; Electrolytes; Hydrogen; Perovskite; Powders; Sintering; Solid state reactions; Carbon dioxide